Compliance of Dental Students toward Infection Control in Dental Teaching Hospital at Thamar University – Yemen - Al-anesi, Mokhtar Saleh; Alhajj, Mohammed Nasser; Al-Basmi, Abdulghani Ali (Brazilian Dental Science, 2017)
Objectives: The aim of the study was to assess the knowledge, attitude and practice related to gender and study level toward infection control among senior dental students. Materials and Methods: The self-administered questionnaire was distributed among the pre-doctoral dental students (4th and 5th levels) in the Dental Teaching Hospital at Thamar University. It included questions related to vaccinations as well as knowledge and practice toward infection control. The collected data was analyzed using Chi-squared test with significant level P-value < 0.05. Results: Response rate was 63%. Distribution of gender among the participants was almost equal with slight increase in number of male subjects. Participated students from 4th-year level were also close to the number of students from 5th-year level. Hepatitis immunization was completed by only 12.9% male students and 17.3% females with no significant difference. Likewise, no significant difference was found among the participants by study level. More than 90% of participants reported always wearing gloves during dental treatment. Unexpectedly, however, using of other protective barriers was low. More than 90% of students, with no significant difference between genders or study levels, reported sterilizing instruments after each dental procedure. Conclusion: The present study showed that the level of knowledge and practice of infection control measures was poor among dental students. The attitude towards infectious control measures was positive, but a greater compliance was needed. Rigorous infection control training for students prior to graduation is also highly recommended. Keywords: Infection control, Compliance, Dental students, Yemen.